Identification of the ultra-short laser parameters during irradiation of thin metal films using the interval lattice Boltzmann method and evolutionary algorithm. (June 2023) - Paruch, Marek; Piasecka-Belkhayat, Alicja; Korczak, Anna
Highlights: Interval latice Boltzmann method (ILBM) is used to solve the microengineering issue. ILBM allowed the consideration of interval relaxation time and boundary conditions. The Boltzmann transport equations are used to describe the energy transfer. The inverse and identification problem were solved by evolutionary algorithm. Abstract: The article presents the one-dimensional numerical modelling of heat transfer in thin metal films irradiated by ultra-short laser pulses. In the mathematical description the relaxation times and the boundary conditions for phonons and electrons are given as interval numbers. The direct problem has been solved by means of the interval lattice Boltzmann method using the rules of directed interval arithmetic, while at the stage of the inverse problem solution, the evolutionary algorithm is applied. On the stage of inverse problems investigations, the evolutionary algorithm coupled with the interval lattice Boltzmann method is used.